Determinants of Accessing Adolescent Health Services Among School Dropout Adolescents in Lombok, Indonesia: A Mixed Method Study - Fitri, Elisa Sulistia; Khotmi, Nurmaulia; Amalia S.J Kahar (International Journal of Health and Social Behavior, 2024)
This study investigates the factors influencing the utilization of adolescent health services among school dropout adolescents in the Sakra subdistrict of East Lombok, Indonesia. Employing a mixed-methods approach, the research combines quantitative data from structured questionnaires with qualitative insights gathered through in-depth interviews. A total of 37 school dropout adolescents, aged 14-19 years, were purposively sampled to participate in the study. The findings from this study underscore the multifaceted factors influencing school dropout adolescents' access to health services in the Sakra subdistrict of East Lombok regency. The six predictors highlighted the importance of knowledge, family support, distance, the role of health professionals, and the recognition of health needs in shaping adolescents' engagement with health services. Addressing these interconnected factors through a comprehensive approach can promote health equity and improve the overall well-being of school dropout adolescents, contributing to healthier communities in the long run.